Analysis of abrB Expression during the Infectious Cycle of Bacillus thuringiensis Reveals Population Heterogeneity - Ben Rejeb, Samia; Lereclus, Didier; Slamti, Leyla (Frontiers in Microbiology, 2017)
Using the model host/pathogen pair Galleria mellonella/Bacillus thuringiensis, we have shown that these bacteria could kill their insect host, survive in its cadaver and form spores by sequentially activating virulence, necrotrophism and sporulation genes. However, the population isolated from the cadavers was heterogeneous, including non-sporulating cells in an unknown physiological state. To characterize these bacteria, we used a transcriptional fusion between the promoter of a gene expressed during early exponential growth (abrB) and a reporter gene encoding a destabilized version of GFP, in combination with a fluorescent reporter of the necrotrophic state. The composition of the bacterial population during infection was then analyzed by flow cytometry. We showed that the PabrB promoter was activated in the population that had turned on the necrotrophic reporter, suggesting a re-entry into vegetative growth. Strikingly, the cells that did not go through the necrotrophic state did not activate the PabrB promoter and appear as a dormant subpopulation. We propose a new model describing the B. thuringiensis cell types during infection.